Systematic Review of Surgical Technique and Tunnel Target Points and Placement in Anatomical Single-Bundle ACL Reconstruction - Iriuchishima, Takanori; Goto, Bunsei (The Journal of Knee Surgery, 2020)
The purpose of this systematic review was to reveal the trend in surgical technique and tunnel targets points and placement in anatomical single-bundle anterior cruciate ligament (ACL) reconstruction. Following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement, data collection was performed. PubMed, EMBASE, and Cochran Review were searched using the terms “anterior cruciate ligament reconstruction,” “anatomic or anatomical,” and “single bundle.” Studies were included when they reported clinical results, surgical technique, and/or tunnel placement evaluation. Laboratory studies, technical reports, case reports, and reviews were excluded from this study. From these full article reviews, graft selection, method of creating the femoral tunnel, and femoral and tibial tunnel target points and placement were evaluated. In the 79 studies included for data evaluation, the selected grafts were: bone patella tendon bone autograft (12%), and hamstring autograft (83%). The reported methods of creating the femoral tunnel were: transportal technique (54%), outside-in technique (15%), and transtibial technique (19%). In the 60 studies reporting tunnel target points, the target point was the center of the femoral footprint (60%), and the center of the anteromedial bundle footprint (22%). In the 23 studies evaluating tunnel placement, the femoral tunnel was placed in a shallow–deep direction (32.3%) and in a high–low direction (30.2%), and the tibial tunnel was placed from the anterior margin of the tibia (38.1%). The results of this systematic review revealed a trend in anatomical single-bundle ACL reconstruction favoring a hamstring tendon with a transportal technique, and a tunnel target point mainly at the center of the ACL footprint. The level of evidence stated is Systematic review of level-III studies.
Keywords: anterior cruciate ligament; single bundle; systematic review; tunnel placement